2023
DOI: 10.1111/pace.14654
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate ventricular fibrillation annotation and defibrillator discharge despite the same tachycardia cycle length in ventricular tachycardia‐1 zone in an Abbott defibrillator – What is the mechanism?

Abstract: Newer devices incorporate advanced algorithms to have more accurate delivery of implantable cardioverter‐defibrillator (ICD) therapy. Newer models of Abbott Implantable cardioverter‐defibrillators like Gallant and Entrant have a new ventricular fibrillation (VF) therapy assurance algorithm. This algorithm has a proven role in avoiding under‐detection of VF where some of the smaller electrograms are under‐sensed. We report a case of ventricular fibrillation therapy assurance (VFTA) algorithm malfunction in a 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The VFTA algorithm has been evaluated retrospectively on 564,353 recorded ventricular tachycardia arrhythmia electrograms from 20,000 devices, and it would have led to a new or earlier HVT in 0.27% (53/20,000) of devices with an increase of inappropriate HVT in 0.07% (14/20,000) devices 8 ; however, to our knowledge, VFTA has not yet been evaluated in prospective clinical trials. One case report 9 described VFTA activation leading to HVT in a monomorphic ventricular tachycardia episode that would has not been treated without VFTA because the arrhythmia rate was lower than the treatment zone cutoffs. The authors suggested the therapy in that case could be inappropriate, but some programming changes could also improve the algorithm’s specificity.…”
Section: Introductionmentioning
confidence: 99%
“…The VFTA algorithm has been evaluated retrospectively on 564,353 recorded ventricular tachycardia arrhythmia electrograms from 20,000 devices, and it would have led to a new or earlier HVT in 0.27% (53/20,000) of devices with an increase of inappropriate HVT in 0.07% (14/20,000) devices 8 ; however, to our knowledge, VFTA has not yet been evaluated in prospective clinical trials. One case report 9 described VFTA activation leading to HVT in a monomorphic ventricular tachycardia episode that would has not been treated without VFTA because the arrhythmia rate was lower than the treatment zone cutoffs. The authors suggested the therapy in that case could be inappropriate, but some programming changes could also improve the algorithm’s specificity.…”
Section: Introductionmentioning
confidence: 99%